The Nabob, National Identity, and Social Performance in Elizabeth Griffith’s A Wife in the Right (1772) - Hilton, Rose (Lumen)

(untitled) (Canadian Society for Eighteenth-Century Studies / Société canadienne d'étude du dix-huitième siècle, 2022)
Elizabeth Griffith’s play A Wife in the Right (1772) features a nabob character, a British man returned from India after having made his fortune through imperial pursuits. This article explores Griffith’s use of the nabob and how the theme of national identity is linked to a discourse around the potential gap between external appearance and internal character in this drama. This article aims to contribute to the growing scholarship surrounding female dramatists in the long eighteenth century by providing an initial step in close reading this drama by Griffith in the context of philosophy and medical writing of the period. Applying, more specifically, Adam Smith’s philosophical and George Cheyne’s medical writing to a close reading of A Wife in the Right, this article reads Griffith’s nabob character and her commentary on national identity as part of a broader social performance of self in this period.